2001
DOI: 10.1246/bcsj.74.1093
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of 9-(Cycloheptatrienylidene)fluorene and Its Derivatives

Abstract: One sesquifulvalene, 9-(cycloheptatrienylidene)fluorene, was found to be composed of a flat fluorenylidene part and a non-planar cycloheptatrienylidene moiety. 1-Substituted 9-(cycloheptatrienylidene)fluorene was not obtained because of a steric repulsion between the 1-substituent and the 7′-hydrogen of the seven-membered ring. Upon consideration of their 13C NMR spectra, the electronic properties of the seven-membered ring are slightly influenced by introducing a substituent (halogen, methoxy group, etc.) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In 2001, Minabe et al reported that 9-CHF was composed of a flat fluorenylidene part and a non-planar cycloheptatrienylidene moiety (Scheme 2). 17 The bond length at C9-C1 0 was 1.360 Å with A mostly double bond character, while the dihedral angle between C9-C1 0 -C2 0 -C3 0 was found to be 1371. This result indicated that a stronger interaction existed in the molecule and the aromaticity was repelled.…”
Section: Structure Of 9-cycloheptatrienylidene Fluorene (9-chf)mentioning
confidence: 93%
See 3 more Smart Citations
“…In 2001, Minabe et al reported that 9-CHF was composed of a flat fluorenylidene part and a non-planar cycloheptatrienylidene moiety (Scheme 2). 17 The bond length at C9-C1 0 was 1.360 Å with A mostly double bond character, while the dihedral angle between C9-C1 0 -C2 0 -C3 0 was found to be 1371. This result indicated that a stronger interaction existed in the molecule and the aromaticity was repelled.…”
Section: Structure Of 9-cycloheptatrienylidene Fluorene (9-chf)mentioning
confidence: 93%
“…A variation in the chemical shifts was observed by 1 H NMR spectra. 17 In fact, the acidification process of 9-CHF could be tracked and measured by an UV-vis spectrophotometer. 36 As a result of the gradual addition of concentrated sulfuric acid or concentrated hydrochloric acid, two new bands at 267 nm and 230 nm were observed with the appearance of three clear isosbestic points at 316 nm, 258 nm, 235 nm (Scheme 4).…”
Section: Structure Of 9-cycloheptatrienylidene Fluorene (9-chf)mentioning
confidence: 99%
See 2 more Smart Citations
“…2,7-Dibromo-9-(cycloheptatrienylidene)fluorene, 2,7-dibromo-9-(2,4,6-cycloheptatrienyl)fluorene, 3 , 5 , 6 , and 8 were prepared and characterized as described previously. , …”
Section: Methodsmentioning
confidence: 99%